Regional Assessment of the Environmental Performance in Ukraine - HOLUBOVA, H. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The impact of economic progress on the environmental performance and public health, urgent problems, and regulatory documents on the environmental protection in Ukraine are highlighted. The statistical data on emission of pollutants in the air and water basin of Ukraine in 2010–2019 are shown. The regional differentiation of the ecological situation of Ukraine in 2019 is analyzed on the basis of the multidimensional average. The index of ecological threat, calculated on the basis of 12 indicators, is offered. The analysis revealed that the industrial regions of Ukraine had the greatest negative impact on the environment: Dnipropetrovsk (1.694) and Donetsk (1.137) regions. The lowest environmental risks were in Chernivtsi (-0.605), Transcarpathia (-0.452), Kherson (-0.376), Ternopil (-0.366), Mykolayiv (-0.342) regions. A typology of Ukrainian regions based on the index of ecological threat is proposed, with breaking the regions into three groups: regions with high, medium, and moderate level of risks. The group with the high level of threats includes two regions of Ukraine, the group with the medium level of risks – 5 regions, and the group with the moderate level of risks – 17 regions. The analysis shows a significant regional differentiation of Ukraine in terms the environmental threat. It confirms the need for a targeted environmental policy focused on the following objectives: greening of production, introduction of alternative energy sources, resource-saving and environmentally friendly technologies, competent waste management, reconstruction and modernization of waste treatment facilities.